Integrated use of fertilizer micro-dosing and Acacia tumida mulching increases millet yield and water use efficiency in Sahelian semi-arid environment - Ibrahim, A.; Abaidoo, Robert C.; Fatondji, D.; Opoku, A. (Springer, 2015)
Limited availability of soil organic amendments and unpredictable rainfall, decrease crop yields drastically in the Sahel. There is, therefore, a need to develop an improved technology for conserving soil moisture and enhancing crop yields in the Sahelian semi-arid environment. A 2-year field experiment was conducted to investigate the mulching effects of Acacia tumida pruning relative to commonly applied organic materials in Niger on millet growth, yields and water use efficiency (WUE) under fertilizer micro-dosing technology. We hypothesized that (1) A. tumida pruning is a suitable mulching alternative for crop residues in the biomass-scarce areas of Niger and (2) combined application of A. tumida mulch and fertilizer micro-dosing increases millet yield and water use efficiency. Two fertilizer micro-dosing options (20 kg DAP ha-1, 60 kg NPK ha-1) and three types of organic mulches (millet straw, A. tumida mulch, and manure) and the relevant control treatments were arranged in factorial experiment organized in a randomized complete block design with four replications. Fertilizer micro-dosing increased millet grain yield on average by 28 %. This millet grain yield increased further by 37 % with combined application of fertilizer micro-dosing and organic mulch. Grain yield increases relative to the unmulched control were 51 % for manure, 46 % for A. tumida mulch and 36 % for millet mulch. Leaf area index and root length density were also greater under mulched plots. Fertilizer micro-dosing increased WUE of millet on average by 24 %, while the addition of A. tumida pruning, manure and millet increased WUE on average 55, 49 and 25 %, respectively. We conclude that combined application of micro-dosing and organic mulch is an effective fertilization strategy to enhance millet yield and water use efficiency in low-input cropping systems and that A. tumida pruning could serve as an appropriate mulching alternative for further increasing crop yields and water use efficiency in the biomass-scarce and drought prone environment such as the Sahel. However, the economic and social implications and the long-term agronomic effects of this agroforestry tree in Sahelian millet based system have to be explored further.